The Role of Accounting Technology in Preventing Cyberfraud: A Systematic Literature Review - Indah, Indah Dwi Novianti; Totok Dewayanto (Asia Pacific Fraud Journal, 2025)
In a state-of-the-art virtual generation, the fast improvement of statistical technology has significantly impacted many industries. This consists of the global economy, but this virtual revolution has additionally delivered another main trouble: the spread of online fraud. Internet fraud is more than just a hazard. This research explores the role of accounting technology in preventing cyber fraud. Based on the theories of the Technology Acceptance Model (TAM) and the Fraud Triangle, this research investigates the accounting technology used to avoid cyber fraud and the effectiveness of the technology in detecting and reducing cyber fraud. Method: A literature review using the PICO approach was used to define the research questions and collect relevant data. The analysis reveals trends in document production, Authors’ contributions, and keywords related to accounting technology. In conclusion, this study provides information for future research to conduct longitudinal studies to assess accounting technology’s effectiveness and long-term challenges.